An Investigation into Hybrid Catamaran Fishing Vessel: Combination of Diesel Engine, Sails and Solar Panels - Pramudya Imawan Santosa; I Ketut Arya Priya Utama (Institut Teknologi Sepuluh Nopember, 2014)
Abstract- Development of hybrid technology for vehicle transportation has been extensively carried out worldwide. At present, the technology has been used in automobile industry in a way to reduce the use of fossil fuels and the effect of toxic gases into the atmosphere. In more details, the hybrid technology applies two sources of energy, namely conventional engine together with the consumption of fossil fuels and solar cell panels in conjunction with the use of battery to store the energy gain. The application of hybrid technology for sea transportation has shown a promising development in the last 5 years. The combination use of sail and engine, which is popularly known as sail assisted engine, has been used to power mono hull fishing vessels by Indonesian fishermen. The attractiveness and successful application of catamaran form for passenger vessels has inspired naval architect to use it as fishing vessels due to its advantages such as having better transverse stability and providing wider deck-space area. The current work describes the development of hybrid technology for a catamaran fishing vessel using the combination of conventional diesel engine, the use of sail and solar-cell panels. In details, it explains the utilization of individual power-source and combination of them to power the catamaran. Discussions include the effectiveness of the combination such as its effect to ship stability and general arrangement of the fishing vessel. Finally, it is discovered that the combination of diesel engine and solar-sails have reached the optimum benefit of the hybrid concept.